2009
DOI: 10.1097/ss.0b013e3181a7e72e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Boron Adsorption-Desorption Hysteresis of Soils

Abstract: Lime is regularly used to increase soil pH, which will increase boron (B) fixation in soils. The effects of raising pH on B adsorption and the reversibility of adsorbed B in acid soils are essential for soil B management. In this study, B adsorption and desorption in limited concentration as a function of pH were measured in five finetextured red soils. Immediately after adsorption of B, four consecutive desorption steps were carried out by successive dilution. The sorption results were described well by the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The Woburn (pH 6.7) and Zegveld (pH 4.7) soils, both having a pH below neutral, were hysteretic in the long-term experiment in contrast to the Hanford soil having a higher pH (7.4), which was not. Our long-term results are in agreement with those of Chen et al (2009), who found increasing hysteresis with decreasing soil pH. Hysteretic behavior can result from the experimental procedure itself.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The Woburn (pH 6.7) and Zegveld (pH 4.7) soils, both having a pH below neutral, were hysteretic in the long-term experiment in contrast to the Hanford soil having a higher pH (7.4), which was not. Our long-term results are in agreement with those of Chen et al (2009), who found increasing hysteresis with decreasing soil pH. Hysteretic behavior can result from the experimental procedure itself.…”
Section: Discussionsupporting
confidence: 94%
“…Boron adsorption by the inorganic soil constituent clay minerals, kaolinite, illite, and montmorillonite, did not exhibit hysteresis (Hingston, 1964). Desorption hysteresis was found to be present at low solution pH and low B concentration and absent at higher solution pH and increasing B concentrations (Meyer and Bloom, 1997;Chen et al, 2009;Majidi et al, 2010). Clearly, the contribution of soil organic matter to the hysteresis of B adsorption-desorption requires further investigation.…”
mentioning
confidence: 74%
“…However, Rosolem and Bíscaro (2007) found that even with the applying of relatively high rates of lime, the B adsorption by soil is only significant in the year that the liming was carried out, so that over time a greater amount of B remains in the soil solution under conditions of being readily absorbed by plants or even being lost by leaching. Similarly, Chen et al (2009) observed that soil re-acidification caused an increase in B desorption, increasing the element's content in solution. Indicating that B adsorption by soils submitted to liming is characterized by a rapid and reversible chemical reaction between the adsorbed and soluble B.…”
Section: Boron Adsorption By Soilsmentioning
confidence: 97%
“…Rosolem and Bíscaro (2007) also found a higher adsorbed B value of 24.2 mg kg -1 at higher pH (5.6) compared to 9.5 mg kg -1 at lower pH (4.5). Various studies have reported that one of the most important factors affecting the adsorption of B in soils is pH (Saltali et al, 2005;Soares et al, 2008;Chen et al, 2009). Boron adsorption by soils increases in the pH range between 3.0 and 9.0, and decreases in the range of 10.0 to 11.5, giving a typical bell curve with an adsorption peak of about 9.0, very close to the boric acid pKa of 9.2 (Goldberg, 1997).…”
Section: Boron Adsorption By Soilsmentioning
confidence: 99%
“…These oxides might have adsorbed added B and lowered the recovery (particularly with L 1 ). Decreased availability of added B with liming below neutrality has been reported by some researchers (Fleming 1980;Chen, Ho, and Lee 2009), whereas others found no definite trends (Gupta and MacLeod 1977) or an increased availability (Mandai, Adhikari, and De 1993).…”
Section: Recovery Of Added Boronmentioning
confidence: 89%